An integrated social studies teaching model based on problem-based and community-based learning to foster 21st century competencies in small primary schools - Phinla, Wipada; Phinla, Wipapan; Mahapoonyanont, Natcha (International Journal of Innovative Research and Scientific Studies, 2025)
This research focused on creating an instructional model for social studies that combines problem-based learning with community-based learning to enhance 21st-century skills in students attending small schools. The study analyzed the effects of implementing this integrated instructional model on developing skills within the target student group.The results indicated the following points: The teaching model combines problem-solving and community involvement and has four main parts: (1) learning actively and on your own; (2) hands-on experiences connected to civic duty, culture, and social life; (3) working together to share ideas; and (4) using what you’ve learned in real-life situations outside of school. The model consists of a five-step instructional process: (1) encountering a social studies situation, (2) integrating social studies thinking, (3) producing social studies work, (4) disseminating social studies outcomes, and (5) consolidating reflective social studies evaluation. The experimental group showed a much better improvement in 21st-century skills after the intervention compared to the control group, with results that are statistically significant at the .05 level. The experimental group demonstrated significantly greater academic achievement in social studies compared to the control group at the .05 level. The overall satisfaction of students was at its highest level with the social studies instructional model that integrates problem-based and community-based learning.